Modern antihyperglycemic therapy: safety and efficacy of glimepiride - Lyudmila Alexandrovna Ruyatkina (Endocrinology Research Centre, 2012)
Current review analyzes pharmacological and clinical aspects of glimepiride from perspective of the evidence-based medicine. We aimedto determine position of glimepiride within modern antihyperglycemic dialectics of safety and efficacy. We also address cardioprotectiveproperties of glimeperide due to its anti-atherogenic activity, capacity to correct endothelial dysfunction and hemostatic system, as wellas absence of inhibitory effect on ischemic preconditioning.